2009
DOI: 10.1614/ws-08-100.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Weed Management Practices on Grapevine Growth and Yield Components

Abstract: The need for reducing costs and making grape production more sustainable has prompted the search for alternative weed control practices that optimize production while maintaining profits. For this reason, it is imperative to understand how different weed management practices modify vine–weed interactions. In the present study, we evaluated the effect on weed growth and Zinfandel grapevine growth and production of five weed control practices: (1) flumioxazin, (2) simazine, (3) cultivation, (4) cover crop, and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 13 publications
4
17
0
Order By: Relevance
“…Drought was partially responsible for the notable decline in plant species richness and density in 2007, when rainfall was only 29% of that in 2006. Sanguankeo et al. (2009) previously reported that in the present study, plant densities and biomass observed in the cultivation, cover crop and control treatments reduced grape yields by 0, 13 and 24% in 2006 and 22, 45 and 48% in 2007, respectively, compared with the herbicide treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drought was partially responsible for the notable decline in plant species richness and density in 2007, when rainfall was only 29% of that in 2006. Sanguankeo et al. (2009) previously reported that in the present study, plant densities and biomass observed in the cultivation, cover crop and control treatments reduced grape yields by 0, 13 and 24% in 2006 and 22, 45 and 48% in 2007, respectively, compared with the herbicide treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that plant density could have played a major role in arthropod diversity (Tables 2 and 3). This result could also be attributed to plant biomass, but this is unlikely because the cover crop and the untreated control had the same plant biomass (Sanguankeo et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2006) and in vineyards (Baumgartner et al. , 2007, 2008), where Sonchus species are considered problematic weeds, in part because they grow into the vine canopy and interfere with harvest (Sanguankeo et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Another result of sustained herbicide use is a shift in weed communities (Elmore et al 1997, Afonso et al 2003, Gago et al 2007, Baumgartner et al 2007, Sanguankeo et al 2009). When annual weeds are controlled through herbicides, perennial weeds can become more common and difficult to control (Elmore et al 1997).…”
Section: Herbicidesmentioning
confidence: 99%